Plasticity of microvascular oxygenation control in rat fast-twitch muscle: effects of experimental creatine depletion - McDonough, Paul; Padilla, Danielle J.; Kano, Yutaka; Musch, Timothy I.; Poole, David C.; Behnke, Brad J. (My University, 2012)
Aging, heart failure and diabetes each compromise the matching of O2 delivery (QO2)-to-metabolic requirements (O2 uptake, VO2) in skeletal muscle such that the O2 pressure driving blood-myocyte O2 flux (microvascular PO2, PmvO2) is reduced and contractile function impaired. In contrast, β-guanidinopropionic acid (β-GPA) treatment improves muscle contractile function, primarily in fast-twitch muscle (Moerland and Kushmerick, 1994). We tested the hypothesis that β-GPA (2% wt/BW in rat chow, 8 wk; n=14) would improve QO2-to-VO2 matching (elevated PmvO2) during contractions (4.5 V @ 1 Hz) in mixed (MG) and white (WG) portions of the gastrocnemius, both predominantly fast-twitch). Compared with control (CON), during contractions PmvO2 fell less following β-GPA (MG -54%, WG -26%, p<0.05), elevating steady-state PmvO2 (CON, MG: 10±2, WG: 9±1; β-GPA, MG 16±2, WG 18±2 mmHg, P<0.05). This reflected an increased QO2/VO2 ratio due primarily to a reduced VO2 in β-GPA muscles. It is likely that this adaptation helps facilitate the β-GPA-induced enhancement of contractile function in fast-twitch muscles.
Keywords: β-guanidinopropionic acid; Microvascular O2 exchange; Muscle fiber type; O2 extraction; Phosphorescence quenching